Principles of gas pricing and their impact on the market for gas cars in Germany - Andreas Seeliger (Mobility in a Globalised World 2012, 2013)
As for any other fuels used for transport or heating, the gas price for final users could be split into three major components: the wholesale price for the resource (including far distance transport by ship or pipeline), taxes and finally a assorted group of mainly smaller price drivers (such as local transport, storage, marketing costs or retail margins). This paper focuses on the gas wholesale price component. It will be demonstrated that due to the traditional pricing system in Germany (net-back pricing based on oil-indexation or "Anlegbarkeit") gas prices have been higher than necessary - at least when assuming a competitive supply and demand based pricing system (like in the US or the UK). Based on the linear optimisation model MAGELAN a hypothetic competitive market price for Germany will be simulated for the period 2000 to 2011 and compared with the actual prices for German gas imports based on the net-back principle. The paper ends with a section discussing the impact of the traditional pricing systems for the German gas mar- ket in general and the situation of gas cars in special. It will be discussed that price regime is only one limiting factor for further development and that massive efforts by the gas industry are needed to push gas cars in Germany.
urn:nbn:de:101:1-2020110913330043863117
Keywords: Q41; Q47; 330; Oil and gas prices; Natural resources; Transport/Mobility; Energy markets